Exploring Lexical Verbs in a Popular Short Story - Nazara, Wa Ozisokhi (STBA Prayoga Padang, 2025)
Abstract This is a syntactic analysis on lexical verbs found in a popular short story. It specifically aimed to identify the types and the forms of lexical verbs in a popular short story The Gift of the Magi. Based distributional method analysis on the data gathered through non-participatory observation, six types of lexical verbs were identified: intensive verbs, transitive verbs, intransitive verbs, prepositional verbs, ditransitive verbs, and complex transitive verbs. Intensive verbs appeared to be the dominant in the short story from which the data were obtained. In terms of forms, five forms were identified: past form, base form, -s form, -ing participle, and -ed participle. The base form occurs as a finite form as well as a non-finite form. The -s form occurs only as a finite form in the third person singular present tense.The past form occurs as a finite form in the past tense. The -ing participle and the -ed participle occurs only as a non-finite form. Past form occurs dominantly in the data analyzed.